Physical activity and motivational predictors of changes in health behavior and health among DM2 and CAD patients. (30th September 2016) - Halvari, H.; Healey, J.; Olafsen, A. H.; Byrkjeland, R.; Deci, E. L.; Williams, G. C.
Abstract : This study tested a physical activity intervention and the self‐determination theory (SDT) process model of health‐behavior change and health among 108 adult patients with both diabetes mellitus type 2 (DM2) and coronary artery disease (CAD). Patients were randomly assigned to an organized physical activity intervention group (led by instructors) or a non‐physical activity control group. At baseline and after 12 months, we measured the following: needs satisfaction, autonomous and controlled motivation for physical activity, perceived competence for physical activity and blood sugar testing, physical activity and blood sugar testing, body weight, glucose control (HbA1c), and self‐perceptions of general health and vitality. The intervention produced, as hypothesized, significant changes in all study variables in favor of the experimental group (Cohen's d effect sizes: 0.23–0.72), except the non‐significant result for controlled motivation and body weight. The data supported the SDT process model, in which the effect of the intervention significantly predicted indirect changes in behavior and health through motivation variables. Considering the moderate to large effects on increases in motivation, behavior, and health, promoting organized physical activity programs that are perceived as need‐supportive may have important health implications for patients with DM2 and CAD.